Prognostic factors in low back pain individuals undergoing steroid and anaesthetic intra-articular facet joint infiltration: a protocol for a prospective, longitudinal, cohort study. Issue 7 (9th July 2019) - Rodrigues, João Carlos; Poetscher, Arthur Werner; Lenza, Mario; Gotfryd, Alberto Ofenhejm; Martins Filho, Délio Eulálio; Rodrigues, Luciano Miller Reis; Garcia, Rodrigo Gobbo; Rosemberg, Laercio Alberto; Barros, Durval do Carmo Santos; Kihara Filho, Eduardo Noda; Ferretti, Mario; Bang, Gilbert Sung Soo
Abstract : Introduction: Lumbar pain of facet origin is a common problem worldwide. For those patients not responding to traditional treatment, one approach may be intra-articular infiltration of corticoid and anaesthetic. However, despite the increasing demand for this procedure, no consensus exists regarding its therapeutic value. The selection of eligible participants may be a determining factor since only those with an inflammatory process will benefit from the use of corticosteroids. This study aims to identify differences in disability, pain and quality of life scores in individuals with and without facet joint inflammation who were diagnosed using MRI. Method and analysis: This prospective cohort will include individuals older than 18 years with a clinical diagnosis of facet syndrome who underwent intra-articular infiltration. Changes in scores of pain, disability and quality of life questionnaires at 1, 3, 6 and 12 months of follow-up compared with baseline will be analysed. An MRI examination performed before infiltration will help to distinguish between exposed (with inflammation) and non-exposed (non-inflammation) groups with facet syndrome. The primary outcome will be the disability questionnaire (Roland Morris), and the secondary outcomes will be the score questionnaires for pain (Visual Analogue Scale), quality of life (EuroQol Quality of Life Questionnaire) and disability (Oswestry). Ethics and dissemination: The Internal Review Board approved this study, which started only after the approval number (5291417.0.0000.0071) was received. All recruited participants will receive a verbal explanation about the purpose of the study, and their decision to participate will be free and voluntary. All participants enrolled in the study will provide a signed informed consent form including confidentiality terms. The results obtained in this study will be presented at national and international conferences and published in peer-reviewed scientific journals to disseminate the knowledge. Trials registration number: NCT03304730; Pre-results.